2018
DOI: 10.1007/s12035-018-1136-3
|View full text |Cite
|
Sign up to set email alerts
|

Docosanoids Promote Neurogenesis and Angiogenesis, Blood-Brain Barrier Integrity, Penumbra Protection, and Neurobehavioral Recovery After Experimental Ischemic Stroke

Abstract: Docosahexaenoic acid (DHA) and neuroprotectin D1 (NPD1) are neuroprotective after experimental ischemic stroke. To explore underlying mechanisms, SD rats underwent 2 h of middle cerebral artery occlusion (MCAo) and treated with DHA (5 mg/kg, IV) or NPD1 (5 μg/per rat, ICV) and vehicles 1 h after. Neuro-behavioral assessments was conducted on days 1, 2, and 3, and on week 1, 2, 3, or 4. BrdU was injected on days 4, 5, and 6, immunohistochemistry was performed on week 2 or 4, MRI on day 7, and lipidomic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 60 publications
4
59
0
Order By: Relevance
“…Dietary administration with docosahexaenoic acid (DHA) has also proven to have anti-inflammatory and neuroprotective effects in cerebral ischemia through the reduction of proinflammatory cytokine expression, such as TNF-α, IL-1β and IL-6; even, a decrease in macrophage and microglial activation and a decrease in leukocyte infiltration to the lesion site [70]. Similar observations were made by Cai et al who noted that macrophage, neutrophil, and T and B lymphocyte infiltration was significantly decreased, besides stimulating an anti-inflammatory macrophage (M2) activation [71]; DHA is also capable of inducing neurogenesis and angiogenesis [72], which makes it a promising molecule for future experimental research.…”
Section: Neurological Deficitsupporting
confidence: 56%
See 1 more Smart Citation
“…Dietary administration with docosahexaenoic acid (DHA) has also proven to have anti-inflammatory and neuroprotective effects in cerebral ischemia through the reduction of proinflammatory cytokine expression, such as TNF-α, IL-1β and IL-6; even, a decrease in macrophage and microglial activation and a decrease in leukocyte infiltration to the lesion site [70]. Similar observations were made by Cai et al who noted that macrophage, neutrophil, and T and B lymphocyte infiltration was significantly decreased, besides stimulating an anti-inflammatory macrophage (M2) activation [71]; DHA is also capable of inducing neurogenesis and angiogenesis [72], which makes it a promising molecule for future experimental research.…”
Section: Neurological Deficitsupporting
confidence: 56%
“…Belayev et al [72] trials in Alzheimer's patients with mild cognitive decline have shown improvements in verbal memory after being treated with a ketogenic diet [73]. Dietary administration with docosahexaenoic acid (DHA) has also proven to have anti-inflammatory and neuroprotective effects in cerebral ischemia through the reduction of proinflammatory cytokine expression, such as TNF-α, IL-1β and IL-6; even, a decrease in macrophage and microglial activation and a decrease in leukocyte infiltration to the lesion site [70].…”
Section: Neurological Deficitmentioning
confidence: 99%
“…PD1 also reduced frequency and seizure duration and prevented weight loss (54). Additionally, intravenous injection of PD1 and its aspirin-triggered isomer (AT-PD1) improved neurological recovery in rat models of ischemic stroke using middle cerebral artery occlusion (51,53).…”
Section: Models Of Neurodegenerative and Neurological Disordersmentioning
confidence: 98%
“…Cellular outcomes were investigated in nine studies both in vivo and in vitro, predominantly using models of AD and ischemia. Intravenous administration of PD1 in vivo reduced immunoglobulin G (IgG) immunoreactivity in the cortex, subcortex, and whole right hemisphere of rats subject to ischemic stroke (53). It also inhibited astrocyte and microglia activation in the penumbra of ischemic rats (51).…”
Section: Cellular Findings Models Of Neurodegenerative and Neurologicmentioning
confidence: 99%
“…The effects of omega-3 FAs (or specific derivatives) in neural tissue have been widely examined in experimental ischemiareperfusion models [55,68,69]. These studies have consistently shown that omega-3 FAs significantly reduce cerebral infarction volume by around 40-50% and are associated with a drastic decrease in the neuroinflammatory response [70,71]. Interestingly, the long-term neurobehavioral recovery in experimental models of ischemic stroke is associated with neuroprotective effects of DHA on both gray and white matter [55].…”
Section: Experimental Modelsmentioning
confidence: 99%